Menegakkan Etika dan Moral Konselor dalam Pelayanan Bimbingan dan Konseling di Lingkungan Pendidikan - Rita wahyu Kusuma; Muhammad Fadhli Anajib; Moh Rizal Khoiruddin; Tamrin Fathoni (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to analyze the implementation of professional ethics and morals of counselors in guidance and counseling services in educational environments and to evaluate challenges and solutions that can improve the quality of counseling services ethically, effectively, and sustainably. This study uses a qualitative approach with a library research method to explore and analyze relevant literature on the ethics and morals of counselors in guidance and counseling in educational environments. Data were collected through searches of journals, books, scientific articles, and related official documents, which were then evaluated and synthesized to produce an in-depth understanding of ethical challenges in counseling practice. The results of this study provide recommendations to strengthen the implementation of ethical and moral principles in guidance and counseling services for the benefit of students. The results of the study indicate that the application of ethical principles of counseling such as confidentiality, fairness, competence, and integrity have become the main guidelines for counselors in providing services to students. Although most counselors have implemented these principles well, there are still several obstacles in terms of a comprehensive understanding of ethics and limitations in professionalism. Therefore, increasing competence and strengthening understanding of ethics are urgent needs to support the quality of guidance and counseling in educational environments.